Experimental investigation on two-phase heat transfer of R-134a during vaporization in a plate heat exchanger with rough surface - Soontarapiromsook, Jutapat; Asirvatham, Lazarus Godson; Dalkilic, Ahmet Selim; Mahian, Omid; Wongwises, Somchai; Ahn, Ho Seon (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
New experimental data were presented on the effect of heat exchanger plate surface roughness, mass flux, average quality, heat flux, and temperature on the evaporative heat transfer coefficient (HTC) and frictional pressure gradient (FPG) of R-134 flowing in a plate heat exchanger (PHE). Three different plate surface roughness of 0.594 mu m, 1.816 mu m, and 2.754 mu m, were used. A commercial herringbone PHE was tested under the counterflow arrangement. The experiments were done at the heat fluxes ranging between 5 and 15 kW/m(2), the mass fluxes were between 67 and 96 kg/m(2)s, and the saturation temperatures ranging from 10 to 20 degrees C. The results showed that the HTC and FRG increased with increasing mass flux, heat flux, average quality and surface roughness. Conversely, they were slightly decreased with an increase in saturation temperature. The optimum thermal performance of a PHE appeared at high plate surface roughness and average quality by about 0.2. The correlations for predicting the Nusselt number and friction factor were proposed for practical applications. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Plate heat exchanger; Evaporation; Roughness; Flow regime map; Heat transfer coefficient; Pressure drop; PRESSURE-DROP; REFRIGERANT VAPORIZATION; FLOW; AMMONIA; CONDENSATION; PERFORMANCE; R-410A; WATER; R134A; Thermodynamics; Engineering; Mechanics